THE EFFECT OF ANIMATED VIDEO MEDIA ABOUT EARLY DETECTION OF BREAST SELF EXAMINATION ON WUS KNOWLEDGE AND BEHAVIOR - Dewi Nopiska Lilis; Yuli Suryanti; Dona Fajrianti; Dini Wahyu Fitria (Jambura Journal of Health Sciences and Research, 2022)
Breast cancer can be detected early by performing a Breast Self-Examination (BSE). Early detection can reduce mortality by 25-30%. Breast self-examination is an examination to look for lumps or changes in the shape of the breast. This can be an indication of breast cancer. This study examines the effect of education on early detection of breast self-examination (BSE) using animated video media on the knowledge and behavior of women of childbearing age (WUS) at Putri Ayu Health Center, Jambi City. This research is an analytic study with a pre-experimental method. The design used in this study was a one group pre-post test. The population of this study were women of childbearing age at Putri Ayu Health Center. The sample in this study were women of childbearing age who came to visit the Putri Ayu Health Center in Jambi City as many as 30 people. After the data was collected, the data were analyzed univariately and bivariately using statistical tests. The results of this study indicate that before being given education with animated videos, most of the respondents had sufficient knowledge as many as 16 respondents (53.33%) and after being given most of them had good knowledge, namely as many as 27 respondents (90%). For behavior before being given education with animated videos, 25 respondents (83.33%) had sufficient behavior and after being given animated videos, 28 respondents (93.33%) had good behavior. There is an effect of education with animated video media on WUS knowledge and behavior regarding early detection of breast self-examination at Putri Ayu Health Center in 2021. It is hoped that it can provide additional information and counseling about BSE examinations and how to carry out BSE examinations that are good and correct.